Validity study of Animal-City Alternating Form Fluency Test in the identification of mild cognitive impairment and Alzheimer's disease - Yun-bo SHI; Qi-hao GUO; Huan YU; Qian-hua ZHAO; Zhen HONG (Chinese Journal of Contemporary Neurology and Neurosurgery, 2015)
Objective To identify the sensitivity and specificity of Animal-City Alternating Form Fluency Test (ACFT) differentiating mild cognitive impairment (MCI) and Alzheimer's disease (AD) from normal controls.  Methods A total of 121 MCI patients, 104 AD patients and 104 healthy controls, who were matched in sex, age and education level, were enrolled in this study. They performed Animal Category Verbal Fluency Test (AFT), City Category Verbal Fluency Test (CFT) and ACFT. A series of standard neuropsychological tests were also administered to reflect episodic memory, verbal ability, working memory, executive function and processing speed. The validity and related influencing factors of ACFT was evaluated.  Results Compared with control group, the ACFT correct number in MCI and AD groups reduced significantly (P = 0.000, 0.000). Receiver operating characteristic (ROC) curve revealed the sensitivity and specificity of ACFT in discriminating MCI (P = 0.012, 0.030) and AD (P = 0.004, 0.003) from normal controls were higher than those of AFT and CFT. There was no correlation of correct number in ACFT with age and education (P > 0.05, for all). The correlations of ACFT with Stroop Color-Word Test (SCWT), Digital Symbol Substitution Test (DSST), Shape Trail Test (STT) and Digit Span Test (DS), all of which reflected attention and executive function, were significantly closer than those of AFT and CFT (P < 0.05, for all). Conclusions ACFT is more efficient in early cognitive impairment identification than the other traditional category verbal fluency tests. It is a new variant form of category verbal fluency test that could assess cognitive function and could be broadly applied in clinical practice.   DOI: 10.3969/j.issn.1672-6731.2015.07.010